Menopausal women’s sense of sexual attractiveness - Bielawska-Batorowicz, Eleonora; Królikowska, Magdalena (Menopause Review/Przegląd Menopauzalny, 2003)
menopause, sexual attractiveness, self-esteem, extraversion